(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The end of the second decade of 21st century can be considered as a breakthrough for Chinese economy and it determines the beginning of a new competitive strategy, based largely on innovative environmental solutions. The main objective of the paper is to investigate the problem of environmental pollutions in China and to point out specific environmental solutions introduced by the Chinese government in recent years. The author is going to emphasize the process of system transformation from an energy – and capital-intensive economy to a knowledge-based economy. The specific objectives are focused on highlighting the role of innovation in maintaining competitiveness on international markets and presenting the consequences of the dynamic development of China after 1978. The author will verify the statement regarding the key role of Chinese government in creating the environmental strategies and implementing them. The research allowed to state that Chinese Communist Party sets the directions for environmental investments and private institutions influence them marginally.